2010
DOI: 10.1007/s00018-010-0462-z
|View full text |Cite
|
Sign up to set email alerts
|

Spider silk proteins: recent advances in recombinant production, structure–function relationships and biomedical applications

Abstract: Spider dragline silk is an outstanding material made up of unique proteins-spidroins. Analysis of the amino acid sequences of full-length spidroins reveals a tripartite composition: an N-terminal non-repetitive domain, a highly repetitive central part composed of approximately 100 polyalanine/glycine rich co-segments and a C-terminal non-repetitive domain. Recent molecular data on the terminal domains suggest that these have different functions. The composite nature of spidroins allows for recombinant producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
152
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(155 citation statements)
references
References 132 publications
0
152
0
3
Order By: Relevance
“…The possibility of tracing varied molecular composition effects on macroscale behavior is realized experimentally through recombinant silk production mimicking the spider spinning process, outlining a powerful multiscale approach that incorporates experiment and simulation. 39 Amino acid sequence Primary protein structure (Å ) The primary protein structure is composed of a sequence of amino acid residues which define the folding of subsequent hierarchical levels. In silk, poly-alanine regions are responsible for stiff cross-linking domains while glycine-rich regions define structures within amorphous domains Basic building block that dictates secondary protein structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility of tracing varied molecular composition effects on macroscale behavior is realized experimentally through recombinant silk production mimicking the spider spinning process, outlining a powerful multiscale approach that incorporates experiment and simulation. 39 Amino acid sequence Primary protein structure (Å ) The primary protein structure is composed of a sequence of amino acid residues which define the folding of subsequent hierarchical levels. In silk, poly-alanine regions are responsible for stiff cross-linking domains while glycine-rich regions define structures within amorphous domains Basic building block that dictates secondary protein structure.…”
Section: Resultsmentioning
confidence: 99%
“…18,20,23 Recent work in genetic engineering and peptide synthesis has been successful in sequencing silk genes and using this information to generate recombinant engineered versions of the natural protein. 38,39 Beta-sheet nanocrystals Secondary protein structure (nm) The secondary protein structure defines local conformations, such as alpha-helices and beta-turns. Beta-sheet crystals in silk have a critical size of 2 nm to 4 nm, exhibiting exceptional strength due to cooperative hydrogen bonding between the sheets.…”
Section: Resultsmentioning
confidence: 99%
“…It is thus generally difficult to maintain the spidroins in solution, especially at high concentration. 215 To mimic natural conditions, high concentrations may be required although it has been found that 15% is an optimal concentration for synthetic spinning. It seems in any case difficult to exceed 20-25 % w/w and, for the moment, difficult to reach the native concentration found in the gland ampulla and to keep the solution stable.…”
Section: Wet Spinningmentioning
confidence: 99%
“…For details see recent reviews on human collagens, 1 mussel pre-collagens, 2,3 silkworm silk, 4,5 and spider silk. [6][7][8][9] Here, we highlight some similarities concerning assembly of the proteins into fibers. All four protein classes exhibit a highly repetitive core region with specific amino acid motifs repeated up to several hundred times.…”
Section: Introductionmentioning
confidence: 99%